Pengaruh Social Media Marketing dan Brand Ambassador terhadap Minat Beli Nacific Dimasa Pandemi Covid-19: - Cucu Tirsa Magda Lena; Ety Dwi Susanti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The COVID-19 pandemic in Indonesia has caused changes in consumer behavior, from buying in person to buying through online. This change in consumer behavior makes companies change their sales system. Nacific is a company that implements an online product purchase system. Therefore, the researcher aims to examine the variables of social media marketing and brand ambassadors on Nacific's interest. The method used in this research is a quantitative survey research, with multiple linear regression analysis. The sampling technique used was non-probability sampling technique. Researchers collect research data by distributing questionnaires to 100 respondents who are consumers and potential customers of Nacific. Research data processing techniques are classical assumption test and hypothesis testing. The results showed that the influence of social media marketing and brand ambassadors on purchase interest was 46.3%. The results of testing the research hypothesis show that social media marketing and brand ambassadors have a simultaneous positive and significant effect on Nacific's purchase interest. Social media marketing and brand ambassadors have a positive and significant partial effect on Nacific's purchase interest. Meanwhile, the brand ambassador has no positive and partially significant effect on Nacific's purchase interest. Keywords: social media marketing, brand ambassador, purchase interest, covid-19 pandemic, nacific